Incidence of Intraocular Inflammation, Retinal Vasculitis, and Retinal Vascular Occlusion Following Intravitreal Brolucizumab in Neovascular Age-Related Macular Degeneration: A Systematic Review and Meta-Analysis - Ida Ayu Laksmi Devi; Sari Marina; Putu Daivi Prakriti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background. Brolucizumab is a humanized single-chain anti-VEGF antibody fragment licensed for neovascular age-related macular degeneration (nAMD). Post-marketing surveillance identified intraocular inflammation (IOI), retinal vasculitis (RV), and retinal vascular occlusion (RVO) as adverse events of special interest, sometimes causing irreversible visual loss. Published incidence estimates range from below 1% to above 10%. We aimed to estimate the pooled cumulative incidence of these events and characterize heterogeneity drivers. Methods. PubMed/MEDLINE, Cochrane CENTRAL, and Google Scholar were searched for phase 3 randomized controlled trials (RCTs), phase IIIb prospective studies, and retrospective/registry studies (≥30 eyes) reporting IOI, RV, or RVO incidence after intravitreal brolucizumab 6 mg in nAMD. A DerSimonian–Laird random-effects model with Freeman–Tukey arcsine transformation was applied; REML, Paule–Mandel, and GLMM (logit link) estimators were used in sensitivity analyses. Results. Ten independent datasets (33,280 brolucizumab-treated eyes; 1,130 events) were included. Pooled cumulative incidence of any IOI/RV/RVO was 5.54% (95% CI 4.23–7.02%; I² = 94.0%; Q = 150.48). Prospective studies yielded higher pooled incidence (8.42%, 95% CI 4.12–14.04%) than retrospective/registry studies (4.35%, 95% CI 3.28–5.56%). Leave-one-out sensitivity ranged 4.98–6.19%. Funnel-plot asymmetry was detected (Egger t = 3.27; p = 0.011). More than 75% of events occurred within six months of the first injection. Conclusion. Cumulative incidence of IOI/RV/RVO after brolucizumab 6 mg in nAMD approached 5.5%, with markedly higher rates under independent adjudication. These findings support careful patient selection, baseline screening for prior IOI history, and intensified monitoring after brolucizumab initiation.